Financial Distress as an Investment Risk Signal: The Role of Profitability, Leverage, and Sales Growth in Textile and Garment Companies on the Indonesia Stock Exchange - Nadia; Reza Pahlevi; Vitriyan Espa (FEBI IAIN Langsa, 2026)
This study aims to examine the effects of profitability, leverage, and sales growth on financial distress among textile and garment companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Although financial distress has been extensively investigated, previous studies have produced inconsistent findings, particularly within the textile and garment industry, which has experienced post-pandemic pressures, rising raw material costs, and increasing competition from imported products. This inconsistency represents the research gap addressed by the present study. A quantitative approach was employed using secondary data obtained from the annual financial statements of 15 companies, resulting in 60 firm-year observations. Logistic regression was used because the dependent variable is dichotomous, distinguishing between financially distressed and non-distressed firms. The findings reveal that profitability (Sig. = 0.119), leverage (Sig. = 0.426), and sales growth (Sig. = 0.568) do not significantly influence financial distress individually. Furthermore, the Omnibus Test indicates that these variables do not simultaneously affect financial distress (Sig. = 0.144). The Nagelkerke R Square value of 0.126 indicates that the model explains only 12.6% of the variation in financial distress, while the remaining 87.4% is explained by other factors outside the model. The novelty of this study lies in applying the Zmijewski model to Indonesia's textile and garment industry during the post-pandemic recovery period by integrating profitability, leverage, and sales growth into a single prediction model. This study contributes to the financial distress literature and provides practical implications for managers, investors, creditors, and regulators in improving early detection and assessment of financial distress risk.